Relative Frequencies and Age Distributions of Breast Lesions at a Thai Tertiary Care Hospital - Poonnoi, Piriya; Sung, Yaeji; Wongwaisayawan, Sansanee; Lapcharoensap, Noppadol; Lertsithichai, Panuwat (The Thai Journal of Surgery, 2016)
Background and Objectives: To determine the relative frequencies and age distributions of various benign and malignant breast lesions at a Thai tertiary care hospital. Material and Methods: Patients who consulted for breast problems at Ramathibodi Hospital during the years 2000 and 2010, and who underwent tissue biopsy or surgical excision were included. Pathological data were retrieved from a patient data base using appropriate codes corresponding to SNOMed (Systematized Nomenclature in Medicine) terminology. Breast lesions were the primary units of analysis. Relative frequencies of breast lesions were calculated and age distributions determined. Results: We included 12,376 lesions. Patients commonly consult and undergo tissue diagnosis for breast lesions during the 2nd and 3rd decades of life, and then again during the 4th and 6th decades, resulting in a bimodal age distribution for both men and women. The most common benign condition in men was hypertrophy, i.e., gynecomastia, for all age groups. The most common benign lesion in women was fibroadenoma, predominantly in the 2nd and 3rd decades of life but continued to be a major finding till the 6th decade. For men with breast cancer, both ductal carcinomas and breast sarcomas were equally common. For women, invasive ductal carcinoma was the most common cancer for all age groups, but breast sarcomas were relatively common during the 2nd and 3rdrd decades of life. For older patients invasive ductal carcinoma was overwhelmingly dominant (> 90% of all invasive cancers). Breast sarcomas accounted for 3% of all invasive cancers in women, if malignant phyllodes tumors were included as well. Thai women with breast cancer were likely younger on average than their Western counterparts. Conclusion: The pattern of age distribution for histologically diagnosed breast lesions was found to be similar for both men and women. Breast sarcomas were conspicuously more common in the present study than those previously reported. Otherwise most breast lesions, especially in women, were distributed according to age in a similar manner as reported elsewhere.